Mulāḥaẓah ‘Ammah ‘an al-Kutub al-Ṣafrā fī al-Ma‘āhid al-Dīnīyah - Mochtar, Affandi (Studia Islamika, 1996)
Islamic intellectual tradition in Indonesia, among others, enriched by literature dars (textbooks) that classical Arabic is still maintained boarding school until today. Literature known as the Kitab Kuning (KK) it marks an important phase that arises from contact archipelago-Middle East more intensive and institutionalized in the scientific world of Islam in Indonesia since the early 16th century until the late 18th century. Until now in the Islamic tradition, the books became major elements that distinguish it from the modern education system. He is transmitted from one generation to the next as if not to appreciate the development and changes in society. But the question; justified in boarding schools of Islamic scholarship so static? If not, why KK used as the main reference for generations? Is not Islam supposed al-Quran and al-Hadith which they referenced?DOI: 10.15408/sdi.v3i2.809